Intense terahertz radiation from relativistic laser–plasma interactions. (2nd November 2016) - Liao, G Q; Li, Y T; Li, C; Liu, H; Zhang, Y H; Jiang, W M; Yuan, X H; Nilsen, J; Ozaki, T; Wang, W M; Sheng, Z M; Neely, D; et al.
Abstract: The development of tabletop intense terahertz (THz) radiation sources is extremely important for THz science and applications. This paper presents our measurements of intense THz radiation from relativistic laser–plasma interactions under different experimental conditions. Several THz generation mechanisms have been proposed and investigated, including coherent transition radiation (CTR) emitted by fast electrons from the target rear surface, transient current radiation at the front of the target, and mode conversion from electron plasma waves (EPWs) to THz waves. The results indicate that relativistic laser plasma is a promising driver of intense THz radiation sources.